Volume 3: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications; Cycle Innovations 1996
DOI: 10.1115/96-gt-195
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Dual-Fuel Injection System for Lean Premixed Industrial Gas Turbines

Abstract: A fuel injection system for industrial gas turbine engines capable of using natural gas and liquid fuel in dry, lean premixed combustion is under development to significantly reduce NOx and CO emissions. The program has resulted in a design capable of operating on DF#2 over the 80 to 100% engine load range meeting the current TA LUFT regulations of 96 ppm (dry, @ 15% O2) NOx and 78 ppm CO. When operating on natural gas the design meets the guaranteed levels of 25 ppm NOx and 50 ppm CO. The desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In this equation, the SMD is proportional to We and Re. In the later research, the more sophisticated SMD correlation was suggested, which is the product of the We and Re with the exponent, as shown in Equation (8). Based on these correlations, many empirical equations related to the SMD have been intended for the jet breakup, and they have been mainly used to describe jet breakup mechanisms with a low injection pressure drop.…”
Section: Generalization Of Effects Of Breakup Mechanisms On Atomizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this equation, the SMD is proportional to We and Re. In the later research, the more sophisticated SMD correlation was suggested, which is the product of the We and Re with the exponent, as shown in Equation (8). Based on these correlations, many empirical equations related to the SMD have been intended for the jet breakup, and they have been mainly used to describe jet breakup mechanisms with a low injection pressure drop.…”
Section: Generalization Of Effects Of Breakup Mechanisms On Atomizationmentioning
confidence: 99%
“…The jet-in-crossflow (JICF) method is a conventional, classical method that is mainly used in air-breathing propulsion systems. A JICF breaks the spray to mix the fuel and air using a large amount of air entering the combustor, and this method has advantages from the perspective of combustion stability, efficiency, and, in particular, emission reductions, which is a critical issue in today's world [1][2][3][4][5][6][7][8][9][10]. In previous studies, empirical correlations have been explored and developed for typical JICF methods, which inject fuel vertically into a horizontal airflow.…”
Section: Introductionmentioning
confidence: 99%
“…An annular prechamber for fuel/air premixing is placed downstream of the air wirier. The prechamber is made up of an outer cylindrical shell (2) and a swirler sleeve (3). A conic contraction (4) is placed downstream of the prechamber, this contraction hampering a flashback within the prechamber.…”
Section: Fig 3 Test Rig Gtn-16 Combustor Sector Modelmentioning
confidence: 99%
“…Many attempts have been made recently by quite a few companies to update gas turbine combustors to achieve a reduction in NOx emissions [1][2][3][4][5][6]. All the proposed engineering approaches involve a substantial gas turbine unit redesign including replacement of casing components and introducing changes in the automatic control system, etc.…”
Section: Introductionmentioning
confidence: 99%